Effects of warming on biological interactions between clams and the seagrass Zostera noltei: A case study using open top chambers. (5th October 2022) - Román, Salvador; Vázquez, Elsa; Román, Marta; Viejo, Rosa M.; Woodin, Sarah A.; Wethey, David S.; Troncoso, Jesús S.; Olabarria, Celia
Abstract: Bivalves and seagrasses can interact through diverse environmentally-modulated mechanisms. To assess the effects of climate warming on bivalve-seagrass interactions, we carried out a pioneering field experiment in which open top chambers (OTCs) were used to increase air and sediment temperature in a shellfish bed in NW Spain during two consecutive spring tides (16 days of exposure to OTCs). The temperature increase produced by OTCs was significant, as observed in the daily maximum and mean temperature and in degree hours, although the difference was greater in air and at the sediment surface (up to 8 °C and 3 °C, respectively) than at 5 cm depth (up to 1 °C). Warming was less acute in boxes with the seagrass Zostera noltei, which acted as a thermal buffer, reducing the mean temperature by 1 °C at the sediment surface in OTC boxes and control boxes (without OTCs). Although the short-term increase in temperature did not greatly affect physiological responses of Z. noltei, the carbohydrate reserves and nutrient content increased in the presence of clams. Growth of the native clam Ruditapes decussatus was significantly slower in OTC boxes with bare sediment, and the seagrass thus buffered the negative effect of warming on growth. The presence of Z. noltei may save clams from having to spend energy to burrow deeper to encounter cooler conditions, leaving more energy available for growth. Conversely, growth of the introduced clam R. philippinarum did not differ between habitats or treatments. Our findings confirm a two-way facilitative interaction that may be particularly important in relation to the resilience of both species in the current context of global warming. Graphical abstract: Image 1 Highlights: Open top chambers significantly increased air and sediment temperatures. The seagrass Z. noltei acted as a thermal buffer during summer low tides. The presence of clams enhanced Z. noltei growth by increasing foliar nutrient content. The presence of Z. noltei enhanced R. decussatus growth under warming conditions.